A compendium of technology key ideas in media and society course UL03102 - Jamsari Hashim; Anna Lynn Abu Bakar (Centre for Academic Excellence and Development (CAED), UMS, 2022)
The knowledge of technology as an essential element in our modern daily life is indeed an acceptable notion. Therefore, the objective of this study is to systematically highlight a set of technology key ideas in the course of Media and Society that is offered from the Liberal Arts Cluster, Centre for the Promotion of Knowledge and Language Learning, Universiti Malaysia Sabah. The method employed in this study was a content analysis by gathering, processing, and analyzing the data. The result of this study produced a key philosophical stance on technology key ideas with tenets of media and society as enshrined in the course content. In conclusion, this study has accomplished its objective as proposed.